Global optimal energy management strategy research for hybrid electric off-road vehicles - Wang, Hong; Huang, Yanjun; Lv, Chen; Khajepour, Amir (Society of Automotive Engineers (SAE), 2017)
Energy management strategy influences the power performance and fuel economy of series hybrid electric tracked bulldozers greatly. In this paper, we will present a procedure for the design of a rule-based power management strategy by defining a cost function, such as minimizing the fuel consumption over a driving cycle. To explore the fuel-saving potential of a series hybrid electric tracked bulldozer, dynamic programming algorithm is then utilized to determine the optimal control actions for a series hybrid powertrain in order to minimize fuel consumption, which can be the benchmark for the assessment of other control strategies. The results from comparing the DP strategy and the rule-based control strategy indicate that there is an approximately 6.8%improvement in fuel economy. Index Terms- Series hybrid electric tracked vehicle, power management strategy, rule-based, dynamic programming.Energy management strategy influences the power performance and fuel economy of series hybrid electric tracked bulldozers greatly. In this paper, we will present a procedure for the design of a rule-based power management strategy by defining a cost function, such as minimizing the fuel consumption over a driving cycle. To explore the fuel-saving potential of a series hybrid electric tracked bulldozer, dynamic programming algorithm is then utilized to determine the optimal control actions for a series hybrid powertrain in order to minimize fuel consumption, which can be the benchmark for the assessment of other control strategies. The results from comparing the DP strategy and the rule-based control strategy indicate that there is an approximately 6.8%improvement in fuel economy. Index Terms- Series hybrid electric tracked vehicle, power management strategy, rule-based, dynamic programming.
Paper originally presented at the WCX17: SAE World Congress Experience, Detroit, 4-6 April 2017
Keywords: Series hybrid electric tracked vehicle; Power management strategy; Dyanmic programming; Rule-based